Enhancement of Mobility and Muscle Strength in Elderly through Ayurveda - Harsha K.P; Tanmay Nigam; Ajai kumar pandey (AYUSHDHARA, 2024)
Geriatrics is a branch of medicine that offers with valuable insights and practices for enhancing mobility and muscle strength in the elderly population. Aging is a natural process of life characterized by the gradual decline of various physiological functions over time. It encompasses biological, psychological, and social changes that occur as individuals with advance of age. Ayurveda has given unique importance to geriatric care since antiquity. Ayurveda has vividly described the measures and interventions that promote mobility and muscle strength among the elderly. Ayurveda recognizes that aging is influenced by the imbalance of Doshas (Vata, Pitta, and Kapha) and advocates restoring equilibrium through herbal medicines, dietary adjustments, lifestyle modifications, and rejuvenation therapies (Rasayanas). Ayurveda emphasizes the importance of diet in promoting musculoskeletal health, advocating for nutritious foods that pacify Vata dosha and support tissue nourishment and repair. Improving the prevention and management of health issues among the elderly can empower them to maintain a high quality of life and preserve their independence in performing daily activities to the fullest extent possible.